IMPROVING THE LONG-TERM PERSONNEL TRAINING SYSTEM IN THE FIELD OF PHYSICAL EDUCATION (American Journal of Pedagogical and Educational Research, 2023)
This article describes the advancement of the scientific and methodological underpinnings of long-term personnel training within the domain of physical education. Recognizing the critical role of effective training systems in shaping competent professionals, the study investigates strategies for improvement to ensure the comprehensive development of individuals pursuing careers in physical education. The author assumes that developing the scientific and methodological foundations of the long-term personnel training system in the field of physical education is imperative for producing competent and adaptable professionals.